POLITIK PEMAKNAAN ATAS PANCASILA PADA ERA PASCAREFORMASI - Hastangka Hastangka (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
This paper discusses about the political meaning over Pancasila which developed in the era of post-reformation. Political meaning addresses two fundamental aspects, namely the legitimacy of power and the legitimacy of values for the political language used by politicians and society. Political meaning is formed by social and reality of politic that develops according to the context of society. The dynamics of social and political life that took place in post-reformation in Indonesia, are interesting to observe and study in the aspects of phenomenology, in particularly, the meaning of the Pancasila ideology. Pancasila, as the object of in this study, has the various existing literature and give the various understandings and interpretations of Pancasila carried out by academics. Pancasila in the aspect of the scope of language is categorized as a variety of political languages. The paper analyzed  by phenomenological analysis method. The results of this study indicate that the Political meaning about Pancasila in the post-reform era was dominated by politicians who legitimized the meaning of Pancasila in various forms of meaning. The politicization process of Pancasila is included in the political, social, religious and cultural spheres.